Integrating Math Values in Da'wah: Fiqh and Maqasid Al-Shariah in the Digital Era - Eko Prayetno; Ibnu Imam Al Ayyubi; Ari Limay Trisno Putra; Tovi Primaresty (Episteme: Jurnal Kajian Mahasiswa, 2026)
This article discusses strategies and challenges of Islamic da’wah in integrating mathematical education values in the digital era, with perspectives from Islamic jurisprudence (Fiqh), Ushul Fiqh, and Maqasid al-Shariah. Amid the rapid development of information technology, Islamic da’wah faces the challenge of reaching the younger generation, which is increasingly exposed to various digital information. One effective approach is to utilize mathematics education as a medium for da’wah, connecting scientific concepts with religious teachings. This research employs a qualitative case study method to explore the strategies and challenges of Islamic da’wah in this context. Data is collected through in-depth interviews with da’wah leaders, educators, mathematics education practitioners, and audiences involved in mathematics-based da’wah. Additionally, document analysis will be conducted on da’wah content disseminated through digital platforms such as social media, websites, and applications. Data collection techniques include in-depth interviews and observations, with data analysis carried out using thematic analysis. This article explores various strategies for integrating Islamic religious values through mathematics learning, as well as challenges that may arise, such as differences in understanding, limited resources, and the need to adapt to constantly evolving technology. By leveraging digital technology, da’wah can be delivered in ways that are more relevant and engaging for the younger generation, allowing religious and scientific education to go hand in hand.